IMPLEMENTASI SUPERVISI KLINIS DI SD NEGERI UJUNG-UJUNG 01 KABUPATEN SEMARANG - Javid Nama Ayu Laksmi (Universitas Kristen Satya Wacana, 2022)
Teachers sometimes have difficulty in teaching. Teachers need guidance in solving the problems. For this reason, clinical supervision is needed to overcome the problems experienced. From the results of the study, clinical supervision proved effective in improving teacher performance, increasing teacher professionalism and improving teacher quality. For this reason, a research was conducted on clinical supervision at SDN Ujung-Ujung 01 to find out the implementation of clinical supervision and the stages in its implementation, as well as to find out the obstacles and benefits of implementing clinical supervision. In this study, we used mixed qualitative and quantitative methods. From this research, it was found that clinical supervision in elementary schools has been implemented well. Although it has been implemented well, there are several obstacles in the implementation of clinical supervision, namely, teachers have not asked for clinical supervision and it takes many times to carry out clinical supervision. However, clinical supervision has benefits to overcome the problems in the classroom. Some recommendations for the headmaster is to socialize clinical supervision and its purpose so teachers are not afraid to be supervised.